Every Man is an Island: Decanonisation and Fragmentation in Reza Ghassemi’s The Nocturnal Harmony of Wood Orchestra - Shabrang, Hoda (Asiatic: IIUM Journal of English Language and Literature, 2020)
Reza Ghassemi’s first Novel, The Nocturnal Harmony of Wood Orchestra, is a unique example of Iranian postmodern novel. First published in the US in 1996 (Nashr-e Ketab-e America) and then by the Iranian publisher Cheshmeh, it was lauded as the Best Novel of the Year 2002 by Hooshang Golshiri Literary Award and as the 2002 Novel of the Year by the Press Critics’ Awards. The protagonist/narrator of the story has fled the post-revolutionary Iran to Paris and ended up dwelling with a variety of typical exilic Iranians – a macrocosm of Iranian society. On the one hand, he has lost his roots; on the other, he cannot adapt to French culture and community. The present study explores the novel in the light of postmodernist point of view and posits that, aside from enjoying features of postmodern fiction in its narrative labyrinths, this work depicts a world with many of its elements rooted in superstitions, religious beliefs and contradictions that are unique to the Iranian mind. In the novel, prominent postmodern elements are traceable and concepts such as metafiction, vicious circles, grand narrative collapse and paranoia are incorporated; however, it is not merely an artificial collection of technical details. After the revolution, many Iranians left the country either because they were related to the previous regime and staying would have been fatal to them, or they could not tolerate the drastic changes in society which made living intolerable. This study aims to show how an Iranian immigrant turns to a specter (he belongs neither to the native culture nor the French) in exile and eventually metamorphoses to a dog. It is in fact a natural consequence of narrating the confusion of a contemporary man in exile who reflects the confusion and turmoil of the dystopian world around him.